ISLAMIC ECONOMIC BEHAVIOR OF GENERATION Z IN RESPONDING TO THE DEVELOPMENT OF THE DIGITAL ECONOMY BASED ON ISLAMIC VALUES - Nunung Nurjanah; Muhammad Iqbal (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: This study aims to synthesize empirical evidence on Generation Z's Islamic economic behavior in the digital economy and to develop an integrated conceptual understanding of digital consumption, Islamic digital investment, and digital philanthropy from the perspective of Islamic economic values. Research Methodology: This study employed a Systematic Literature Review (SLR) based on the PRISMA 2020 guidelines. Literature was retrieved from the Scopus, Google Scholar (via Publish or Perish), and Garuda databases in June 2026. Following the identification, screening, eligibility, and inclusion processes, 18 peer-reviewed articles published between 2020 and 2026 were selected and synthesized using thematic analysis. Results: The findings identify three interconnected dimensions of Generation Z's Islamic economic behavior: digital consumption, Islamic digital investment, and digital philanthropy. The synthesis demonstrates that Islamic economic behavior is shaped through the interaction of digital technology, Islamic financial literacy, digital culture, religiosity, and the internalization of Islamic values. While technological advancement has expanded access to Islamic financial services, digital philanthropy exhibits stronger alignment with Islamic values than digital consumption and investment activities. Conclusions: Islamic economic behavior among Generation Z is not determined by technological advancement alone but by the integration of technological, financial, social, and religious dimensions. Strengthening the Islamic digital economy therefore requires the integration of technological innovation with ethical awareness and value-based Islamic financial education Limitations: : This review was limited to peer-reviewed articles indexed in Scopus, Google Scholar, and Garuda published between 2020 and 2026 and did not include quantitative meta-analysis. Contributions: This study develops an integrated conceptual understanding of Generation Z's Islamic economic behavior in the digital economy and provides practical insights for policymakers, Islamic financial institutions, fintech providers, and researchers in promoting an inclusive, ethical, and sustainable Islamic digital economic ecosystem.